AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL 70% DAN INFUSA DAUN KECIPIR (Psophocarpus tetragonolobus (L.) DC.) DENGAN METODE PERENDAMAN RADIKAL BEBAS - Eem Masaenah; Anna Priangani Roswiem; Devina Putri (Jurnal Farmamedika (Pharmamedika Journal), 2019)
Winged leaf (Psophocarpus tetragonolobus (L.) DC.) has been known to contain vitamin C compounds which can be efficacious as antioxidants. The aims of this study was determine the secondary metabolites contained in 70% ethanol extract and winged leaf (Psophocarpus tetragonolobus (L.) DC) infusion and to test the antioxidant activity of 70% ethanol extract and winged leaf infusion (Psophocarpus tetragonolobus (L.) DC). ) with the free radical reduction method using DPPH. Ethanol extract of 70% winged leaf (Psophocarpus tetragonolobus (L.) DC.) was made with a series of concentrations of 10, 15, 20, 25, 30 ppm and infusion of winged leaf (Psophocarpus tetragonolobus (L.) DC) with a series of concentrations of 75, 100, 125, 150, 175 ppm are both dissolved with methanol pro analysis and DPPH, then their absorbance is measured using a UV-Vis spectrophotometer at a wavelength of 517 nm. Ethanol extract of 70% winged leaf (Psophocarpus tetragonolobus (L.) DC.) Contains flavonoid, saponin, tannin, steroids and winged leaf infusion (Psophocarpus tetragonolobus (L.) DC) contains flavonoid, saponin, tannin. Ethanol extract of 70% winged leaf (Psophocarpus tetragonolobus (L.) DC.) Has antioxidant activity with IC50 value of 22.12 ppm (very strong) and winged leaf infusion (Psophocarpus tetragonolobus (L.) DC.) of 167.03 ppm (weak) and vitamin C as a positive control of 6.82 ppm (very strong).